2008
DOI: 10.1016/j.cell.2008.03.027
|View full text |Cite
|
Sign up to set email alerts
|

The Epithelial-Mesenchymal Transition Generates Cells with Properties of Stem Cells

Abstract: The epithelial-mesenchymal transition (EMT) is a key developmental program that is often activated during cancer invasion and metastasis. We here report that the induction of an EMT in immortalized human mammary epithelial cells (HMLEs) results in the acquisition of mesenchymal traits and in the expression of stem-cell markers. Furthermore, we show that those cells have an increased ability to form mammospheres, a property associated with mammary epithelial stem cells. Independent of this, stem cell-like cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

376
7,779
24
66

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 7,774 publications
(8,245 citation statements)
references
References 42 publications
376
7,779
24
66
Order By: Relevance
“…Trastuzumab has proven efficacy as first‐line treatment of advanced HER2 + breast cancer patients. However, initial benefit lasts not long before the occurrence of conversion, resulting in an acquired resistance 27. Therefore, breakthroughs were needed in the finding of effective therapeutic targets and overcome of acquired trastuzumab resistance, especially for patients with HER2 + sites.…”
Section: Discussionmentioning
confidence: 99%
“…Trastuzumab has proven efficacy as first‐line treatment of advanced HER2 + breast cancer patients. However, initial benefit lasts not long before the occurrence of conversion, resulting in an acquired resistance 27. Therefore, breakthroughs were needed in the finding of effective therapeutic targets and overcome of acquired trastuzumab resistance, especially for patients with HER2 + sites.…”
Section: Discussionmentioning
confidence: 99%
“…The EMT is a critical regulator of the CSC phenotype, and studies have reported that the EMT can generate tumor cells, and even normal cells, with CSC‐like properties 3, 27, 28. We had proved that FLI‐1 correlates positively with the EMT, and silencing FLI‐1 inhibited the expression of mesenchymal markers.…”
Section: Resultsmentioning
confidence: 90%
“…CSCs 33, 34, 60 and EMT 35, 37, 42, 43 both fuel cancer progression and mediate drug resistance. The transmembranous glycoprotein EpCAM exerts distinct and partially paradoxical functions in CSCs and EMT: while CSCs from epithelial‐derived tumors express high levels of EpCAM, EMT cells have downregulated the expression of this key epithelial denominator.…”
Section: Resultsmentioning
confidence: 99%
“…Accumulating evidence suggests a strong and possibly causal link between EMT and the acquisition of stem cell properties in both normal and malignant epithelial cells 42, 43. In addition, EpCAM, along with other markers such as E‐cadherin and cytokeratins, defines a key denominator of the epithelial cell state.…”
Section: Interdependence Of Epcam Emt and Cscsmentioning
confidence: 99%